2016
DOI: 10.2340/00015555-2235
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Study of Sensitive Skin

Abstract: Sensitive skin is a clinical syndrome characterized by the occurrence of unpleasant sensations, such as pruritus, burning or pain, in response to various factors, including skincare products, water, cold, heat, or other physical and/or chemical factors. Although these symptoms suggest inflammation and the activation of peripheral innervation, the pathophysiogeny of sensitive skin remains unknown. We systematically analysed cutaneous biopsies from 50 healthy women with non-sensitive or sensitive skin and demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 40 publications
6
89
0
6
Order By: Relevance
“…Indeed, histological observations have indicated that epidermal nerve fibres are present at higher densities in the skin of patients with itchy psoriasis (Nakamura et al , 2003; Taneda et al , 2011), lichenified atopic skin (Urashima and Mihara, 1998), photodamaged skin (Toyoda et al , 2005) and in a mouse model of xerosis (Tominaga et al , 2007), than in healthy individuals. On the other hand, IENFD have been shown to be reduced in conditions such as sensitive skin (Buhé et al , 2016), prurigo nodularis (Schuhknecht et al , 2011), and in a case report of grafted skin (Zeidler et al , 2016). It could be interesting to see if these changes in skin innervation can lead to pain of neuropathic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, histological observations have indicated that epidermal nerve fibres are present at higher densities in the skin of patients with itchy psoriasis (Nakamura et al , 2003; Taneda et al , 2011), lichenified atopic skin (Urashima and Mihara, 1998), photodamaged skin (Toyoda et al , 2005) and in a mouse model of xerosis (Tominaga et al , 2007), than in healthy individuals. On the other hand, IENFD have been shown to be reduced in conditions such as sensitive skin (Buhé et al , 2016), prurigo nodularis (Schuhknecht et al , 2011), and in a case report of grafted skin (Zeidler et al , 2016). It could be interesting to see if these changes in skin innervation can lead to pain of neuropathic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the pathophysiology of skin sensitivity resembles that of neuropathic pruritus within the context of small fiber neuropathy, and that environmental factors may alter skin innervation 17. Reactive skin can appear normal or accompanied by erythema, can affect all body locations, particularly the face, and may worsen in the presence of a simultaneous dermatosis 16…”
Section: Discussionmentioning
confidence: 99%
“…The neuropathic origin of sensitive skin may be a result of degeneration of intraepidermal nerve fibers. 39 …”
Section: Skincare: Current State Of Playmentioning
confidence: 99%